The emergence of the regulatory state: The political economy of Turkish banking reforms in the age of post-Washington consensus - Caner Bakır; Ziya Öniş (TÜSİAD-Koç University Economic Research Forum, 2009)
The new era of Post-Washington Consensus (PWC) promoted under the auspices of multilateral organizations such as IMF and the World Bank centres on the need to develop strong regulatory institutions, especially the realm of banking and finance in developing countries. By focusing on the Turkish experience in the aftermath of the 2001 crisis, the article identifies the positive features of the new era the PWC in terms of the banking sector which as a result has become much more robust in terms of its ability to withstand external shocks and to avert future financial crises. At the same time, however, the article highlights some of the limitations of the new era. Important limitations are identified in terms of the distributional impact of the regulatory reforms with the banking sector and notably the foreign banks emerging as the major beneficiaries of this process. Additional limitations are observed in the areas of consumer protection and competition regulation. These weaknesses, in turn, highlight the limits of the emerging regulatory state in the era of the PWC. Similarly, significant weaknesses are evident in terms of the ability of the banking system to finance the real economy, and notably the small and medium sized businesses.
Keywords: G21; G28; 330; regulatory state; post-Washington consensus; banking; Turkey; Bankenreform; Bankenkrise; Bankgeschäft; Türkei